AN OVERVIEW OF VISCOSUPPLEMENTS: THERAPEUTIC MODALITY FOR THE AILMENT OF OSTEOARTHRITIS - Kapoor, Devesh; Lad, Chaitali; Vyas, Ruchi; Patel, Manish (Journal of Drug Delivery and Therapeutics, 2016)
Osteoarthritis is a multifarious joint disease and is caused by inflammatory mediators, along with a procedure of wear and tear of cartilage. Osteoarthritis outcome in cartilage degradation, synovial inflammation, subchondral bone eburnation, degeneration of menisci, and capsular hypertrophy, which takes part in the pathogenesis of Osteoarthritis. Pain is the leading symptom of Osteoarthritis. However the precise mechanism causing pain is multifactorial and is still not well known. Viscosupplementation with intraarticular hylauronic acid promotes chondrocyte hyaluronic acid synthesis and prevents the additional cartilage degradation and may possible help to promote the cartilage regeneration. It is also postulated to diminish the production of inflammatory mediators and matrix metalloproteinase involved in Osteoarthritis. Viscosupplementation decline osteoarthritis symptoms in early to judicious Osteoarthritis, and improves functional outcome, if other conservative treatment modalities are ineffective. Hyaluronic acid (HA) is the major constituent of a 1-Ââ€2Î¼m layer on the surface of articular cartilage; it is also a major constituent of synovial fluid. HA has many properties including exerting an anti-inflammatory effect, it acts as a lubricant when movements in the joint are slow and as a shock absorber when movements are fast effect. Viscosupplementation relieves the symptoms of osteoarthritis of the knee, and this therapeutic effect may last several weeks. However, it is apparently not much greater than that of placebo and, according to some studies, it barely reaches clinical significance. Its pain-relieving effect seems comparable to that of other non-surgical options. The modest clinical benefit of viscosupplementation may never be great enough to outweigh its disadvantages, which include slow onset of action, the need for several weekly injections, the low but present risk of adverse reactions and the relatively high cost of this treatment. It helps in improving the function in early osteoarthritis knee joint and might delay the need for future knee surgery Keywords: Joint disorders, intraarticular hylauronic acid, non-steroidal anti-inflammatory drugs, osteoarthritis Â